Gatekeeping and referral of patients holding private health insurance: a survey among general practitioners in Norway - Jørgen Breivold; Karin Isaksson Rø; Stein Nilsen; Merethe Kristine Kousgaard Andersen; Jørgen Nexøe; Stefán Hjörleifsson (Taylor & Francis Group, 2024)
Objective Private health insurance is becoming more common in Norway. The aim of this study was to investigate GPs' opinions on private health insurance, and their experiences from consultations where health insurance can affect decisions about referring.Design A web based cross-sectional survey.Setting Norwegian general practice.Subjects All GPs in Norway were in 2019 invited to participate in an online survey.Main outcome measures The GPs' opinions and experiences regarding health insurance were reported as proportions. Multiple logistic regression was used to test associations between how frequently GPs refer patients without further considerations and variables concerning their characteristics, opinions, and experiences.Results Of 1,309 GPs (response rate 27%), 93% stated that private health insurance raises the risk of overtreatment and 90% considered such insurance to contribute to inequality in health. Frequently being pressured to refer in the absence of a medical indication was reported by 42%. Moreover, 28% often or always chose to refer patients without further consideration, and this was associated with perceptions of pressure with an adjusted odds ratio (AOR) of 3.80, 95% confidence interval (CI) 2.73-5.29, and unpleasant reactions from patients following refusals (AOR 1.63, 95% CI 1.14-2.33).Conclusion Although most participating GPs associated private health insurance with overtreatment and inequality in health, more than one in four choose to refer without further consideration. GPs' experience of pressure to refer and negative reactions from patients when they consider referrals not to be medically indicated, raises the risk of medical overuse for patients holding private health insurance.